(untitled) (Research, Society and Development, 2021)
Objective: Create and validate a podcast for dental surgeons as a guide after a dental avulsion. The validation was done through Google forms. Nine expert judges participated, following four aspects: characterization of the judges, content, functionality and appearance. The quantitative analysis was performed with Excel software to calculate the content validity index. Method: Methodological study with a quantitative and validation approach, carried out in three stages: integrative review of the literature; technology construction; validation of a post-avulsion podcast presented to nine expert judges. A Likert scale was used for data collection. For the analysis, a content validity index ≥ 0.75 was adopted. Results: The Content Validity Index presented values ​​of 0.84% ​​in its structure and presentation, 099% of high relevance for expert judges. Conclusion: The “Al Dente” podcast contains important information on dental reimplantation after an avulsion, resulting in preventive measures that directly influence health services.